Oxidative Stress Parameters and Its Associations With Arterial Stiffness in Competitive Powerlifting Athletes After 12-Week Supervised Strength Training. Issue 7 (July 2019) - Jürgenson, Janno; Serg, Martin; Kampus, Priit; Kals, Jaak; Zagura, Maksim; Viru, Mehis; Zilmer, Kersti; Zilmer, Mihkel; Eha, Jaan; Unt, Eve
Abstract : Abstract: Jürgenson, J, Serg, M, Kampus, P, Kals, J, Zagura, M, Viru, M, Zilmer, K, Zilmer, M, Eha, J, and Unt, E. Oxidative stress parameters and its associations with arterial stiffness in competitive powerlifting athletes after 12-week supervised strength training. J Strength Cond Res 33(7): 1816–1822, 2019—Available studies have not revealed a clear understanding of the impact of intensive strength training on arterial stiffness and oxidative stress (OxS) parameters, which may have a significant impact on further cardiovascular health of an athlete. The purpose of this study was to evaluate the effect of a 12-week supervised strength training program (SSTP) on oxidative stress indices and its relationship with arterial stiffness in powerlifting athletes. A total of 19 men (28 ± 6 years) exercised for 12 weeks (4 days per week with intensity 60–90% assessed from 1 repetition maximum, 90–120 minutes per session). Oxidative stress parameters and arterial stiffness (SphygmoCor 7.1) were measured before and after SSTP. The study results showed that total peroxide concentration increased and total antioxidant capacity decreased significantly after SSTP. There were no significant changes in carotid-femoral pulse wave velocity (cfPWV) or in the augmentation index. Correlation analysis revealed that the magnitude of the increase of cfPWV was significantly related to the increase of OxS. The current study demonstrated that a 12-week SSTP in powerlifting athletes produced significant changes in OxS indices, which were positively related to increased aortic stiffness. This novel finding may have significant implications about the effect of OxS on cardiovascular health after high-intensity strength training. Furthermore, strength and conditioningcoaches may have to consider the long-term exercise-induced changes in OxS on an individual level, where increased OxS leads to impaired arterial stiffness and cardiovascular health.